Autologous transplantation versus allogeneic transplantation in patients with follicular lymphoma experiencing early treatment failure. Issue 12 (12th April 2018) - Smith, Sonali M.; Godfrey, James; Ahn, Kwang Woo; DiGilio, Alyssa; Ahmed, Sairah; Agrawal, Vaibhav; Bachanova, Veronika; Bacher, Ulrike; Bashey, Asad; Bolaños‐Meade, Javier; Cairo, Mitchell; Chen, Andy; et al.
Abstract : BACKGROUND: Early treatment failure (ETF) in follicular lymphoma (FL), defined as relapse or progression within 2 years of frontline chemoimmunotherapy, is a newly recognized marker of poor survival and identifies a high‐risk group of patients with an expected 5‐year overall survival (OS) rate of approximately 50%. Transplantation is an established option for relapsed FL, but its efficacy in this specific ETF FL population has not been previously evaluated. METHODS: This study compared autologous hematopoietic stem cell transplantation (auto‐HCT) with either matched sibling donor (MSD) or matched unrelated donor (MUD) allogeneic hematopoietic cell transplantation (allo‐HCT) as the first transplantation approach for patients with ETF FL (age ≥ 18 years) undergoing auto‐HCT or allo‐HCT between 2002 and 2014. The primary endpoint was OS. The secondary endpoints were progression‐free survival, relapse, and nonrelapse mortality (NRM). RESULTS: Four hundred forty FL patients had ETF (auto‐HCT, 240; MSD hematopoietic stem cell transplantation [HCT], 105; and MUD HCT, 95). With a median follow‐up of 69 to 73 months, the adjusted probability of 5‐year OS was significantly higher after auto‐HCT (70%) or MSD HCT (73%) versus MUD HCT (49%; P  = .0008). The 5‐year adjusted probability of NRM was significantly lower for auto‐HCT (5%) versus MSD (17%) or MUD HCT (33%; P  < .0001). The 5‐year adjusted probability of disease relapse was lower with MSD (31%) or MUD HCT (23%) versus auto‐HCT (58%; P  < .0001). CONCLUSIONS: Patients with high‐risk FL, as defined by ETF, undergoing auto‐HCT for FL have low NRM and a promising 5‐year OS rate (70%). MSD HCT has lower relapse rates than auto‐HCT but similar OS. Cancer 2018;124:2541‐51. © 2018 American Cancer Society . Abstract : Early treatment failure is a predictor of poor outcomes for follicular lymphoma patients with a 5‐year survival rate of only 50%. Hematopoietic stem cell transplantation has not been specifically assessed in this population. This Center for International Blood and Marrow Transplant Research analysis has found that hematopoietic stem cell transplantation is associated with a 70% long‐term survival rate for follicular lymphoma patients with early treatment failure, and it supports transplantation as an excellent treatment option. See also pages 2484‐7.